Design and implementation of a multi-layered security platform for IoT device management - Wong, Zhi Lin; Abdul Rahman, Siti Husna; Zainuddin, Ahmad Anwar (IEEE, 2025)
The rapid proliferation of Internet of Things (IoT) devices has introduced substantial challenges related to security, scalability, and centralized management particularly within open-source ecosystems. This study presents the design and implementation of an open-source IoT Device Management Platform enhanced with a multi-layered security architecture. The platform incorporates Time-Based One-Time Password (TOTP) authentication and real-time push notifications to strengthen user verification and access control. Additional protective measures, such as frontend input validation and backend rate-limiting middleware, are integrated to defend against common web-based attacks, including brute-force and denial-of-service attempts. Built on a Django backend and Vue.js frontend, the system offers an efficient and user-friendly interface for real-time device monitoring and control. Performance and security evaluations, including stress testing under high concurrency, confirm the platform’s robustness, responsiveness, and resistance to abuse. As an open-source initiative, the system promotes community-driven development and extensibility. Future enhancements will explore the integration of CAPTCHA, real-time alerting, anomaly detection, and broader protocol support to further advance secure IoT management practices.